Respuesta :
Answer:
The equivalent expressions are:
[tex]b1=\frac{2a}{h}-b2[/tex]
[tex]h=\frac{2a}{b1+b2}[/tex]
Step-by-step explanation:
Given equation for finding area of a trapezoid:
[tex]a=\frac{1}{2}(b1+b2)h\\[/tex]
where [tex]a[/tex] represents area, [tex]h[/tex] represents height and [tex]b1\ and\ b2[/tex] represents the base lengths of the trapezoid.
Evaluating [tex]h[/tex] by rearranging the equation to find an equivalent equation.
Multiplying both sides by 2.
[tex]2\times a=2\times\frac{1}{2}(b1+b2)h[/tex]
[tex]2a=(b1+b2)h[/tex]
Dividing both sides by [tex]b1+b2[/tex]
[tex]\frac{2a}{b1+b2}=\frac{(b1+b2)h}{b1+b2}[/tex]
[tex]\frac{2a}{b1+b2}=h[/tex]
[tex]\therefore h=\frac{2a}{b1+b2}[/tex]
Evaluating [tex]b1[/tex] by rearranging the equation to find an equivalent equation.
Multiplying both sides by 2.
[tex]2\times a=2\times\frac{1}{2}(b1+b2)h[/tex]
[tex]2a=(b1+b2)h[/tex]
Dividing both sides by [tex]h[/tex]
[tex]\frac{2a}{h}=\frac{(b1+b2)h}{h}[/tex]
[tex]\frac{2a}{h}=b1+b2[/tex]
Subtracting both sides by [tex]b2[/tex]
[tex]\frac{2a}{h}-b2=b1+b2-b2[/tex]
[tex]\frac{2a}{h}-b2=b1[/tex]
[tex]\therefore b1=\frac{2a}{h}-b2[/tex]